Thailand Economic Monitor, February 2014 - World Bank (Bangkok, 2014)
The Thai economy has been recovering slowly from the global financial crisis compared to countries like Malaysia and China. Growth in 2013 is projected to be 3 percent with slower than expected performance in all components of gross domestic product (GDP) - consumption, investment, next exports, and government spending. Growth is projected to be 4.0 percent in 2014 as the global economy recovers. Exports should accelerate and may well be helped by the tapering of the United States (U.S.) quantitative easing (QE) as the baht depreciates. Taking a longer perspective, there remains visible inequality in public service delivery and human achievement outcomes. Addressing the regional disparities is important for Thailand not only from a social equity perspective, but also from a competitiveness and economic growth perspective. As the population ages, Thailand is seeking to move to a high income economy. Such a transition will require a much broader base of healthy and high skilled citizens. Suggested policy responses include: (a) rebalancing public spending regionally, (b) improving the functioning of local administration by devolving more responsibility to local levels, and (c) supporting greater accountability at the local level. This report is divided into two parts: part one presents macroeconomic developments in 2013 and 2014; and part two deals with equitable public service provision in Thailand.